Persistent neuropsychiatric symptoms after COVID-19: a systematic review and meta-analysis. Issue 1 (17th December 2021) - Badenoch, James B.; Rengasamy, Emma R.; Watson, Cameron; Jansen, Katrin; Chakraborty, Stuti; Sundaram, Ritika D.; Hafeez, Danish; Burchill, Ella; Saini, Aman; Thomas, Lucretia; Cross, Benjamin; Hunt, Camille K.; et al.
Abstract: The nature and extent of persistent neuropsychiatric symptoms after COVID-19 are not established. To help inform mental health service planning in the pandemic recovery phase, we systematically determined the prevalence of neuropsychiatric symptoms in survivors of COVID-19. For this pre-registered systematic review and meta-analysis (PROSPERO ID CRD42021239750), we searched MEDLINE, EMBASE, CINAHL and PsycINFO to 20 February 2021, plus our own curated database. We included peer-reviewed studies reporting neuropsychiatric symptoms at post-acute or later time-points after COVID-19 infection and in control groups where available. For each study, a minimum of two authors extracted summary data. For each symptom, we calculated a pooled prevalence using generalized linear mixed models. Heterogeneity was measured with I 2 . Subgroup analyses were conducted for COVID-19 hospitalization, severity and duration of follow-up. From 2844 unique titles, we included 51 studies ( n = 18 917 patients). The mean duration of follow-up after COVID-19 was 77 days (range 14–182 days). Study quality was most commonly moderate. The most prevalent neuropsychiatric symptom was sleep disturbance [pooled prevalence = 27.4% (95% confidence interval 21.4–34.4%)], followed by fatigue [24.4% (17.5–32.9%)], objective cognitive impairment [20.2% (10.3–35.7%)], anxiety [19.1% (13.3–26.8%)] and post-traumatic stress [15.7% (9.9–24.1%)]. Only two studies reported symptoms in control groups, both reporting higher frequencies in COVID-19 survivors versus controls. Between-study heterogeneity was high ( I 2 = 79.6–98.6%). There was little or no evidence of differential symptom prevalence based on hospitalization status, severity or follow-up duration. Neuropsychiatric symptoms are common and persistent after recovery from COVID-19. The literature on longer-term consequences is still maturing but indicates a particularly high prevalence of insomnia, fatigue, cognitive impairment and anxiety disorders in the first 6 months after infection. Abstract : In a systematic review and meta-analysis, Badenoch et al. report frequent neuropsychiatric symptoms persisting up to 6 months after COVID-19, including insomnia, fatigue, anxiety, post-traumatic symptoms, cognitive impairment and mood disorder. Health services should plan for a high requirement for multidisciplinary services (including neurological, neuropsychiatric and psychological management) after COVID-19. Graphical Abstract: Graphical Abstract